Electromagnetic waves propagation in dust storms at millimetre wave band - Abdulwaheed, Musa; Bashir, Saad Osman (Scholarlink Research Institute Journals, 2013)
The effects of dust storms on propagation of electromagnetic wave at millimeter wave band are investigated. The propagation at millimeter wave band is affected by dust particles by way of signal attenuation. Formula for evaluating the wave attenuation at higher frequencies in a dusty medium is therefore developed in this work. The formula is based on the complex forward scattering amplitude of spherical dust particles using Rayleigh method. Three conditions are set to validate the suitability of the method for the model. It is shown that the Rayleigh approximation is valid for determining the scattering of spherical dust particles for the particle sizes and frequency range considered. The wave attenuation expression is proposed in terms of wavelength, visibility and complex permittivity. Attenuation results obtained are compared with some already published results. It is found that the attenuation by the proposed formula and the published formulae show close agreement. Attenuation in dry dust is only significant when the visibility becomes severe or at lower millimetric wave bands.